Therapeutic Potential of Vasoactive Intestinal Peptide and its Derivative Stearyl-Norleucine-VIP in Inflammation-Induced Osteolysis - Eger, Michal; Liron, Tamar; Hiram-Bab, Sahar; Awida, Zamzam; Giladi, Eliezer; Dangoor, David; Fridkin, Mati; Kohavi, David; Gozes, Illana; Gabet, Yankel (Frontiers in Pharmacology, 2021)
The common use in dental and orthopedic implants calls for special attention to the immune response leading to peri-prosthetic bone loss and implant failure. In addition to the well-established microbial etiology for oral implant failure, wear debris and in particular titanium (Ti) particles (TiP) in the implant vicinity are an important trigger of inflammation and activation of bone resorption around oral and orthopedic implants, presenting an unmet medical need. Here, we employed bacterial-derived lipopolysaccharides (LPS) to model infection paralleled by TiP to model aseptic inflammation and osteolysis. We assessed inflammation in vitro by measuring IL1β, IL6 and TNFβ mRNA expression in primary macrophages, osteoclastogenesis in RANKL-induced bone marrow derived pre osteoclasts and osteolysis in vivo in a mouse calvarial model. We also assessed the trans-epithelial penetrability and safety of the tested compound in rats. Our results show that a lipophilic super-active derivative of vasoactive intestinal peptide (VIP), namely stearyl-norleucine-VIP (SNV) presented superior anti-inflammatory and anti-osteoclastogenic effects compared to VIP in vitro. In the bacterial infection model (LPS), SNV significantly reduced IL1β expression, while VIP increased IL6 expression. In the aseptic models of inflammation-induced osteolysis, SNV showed greater suppression of in vitro osteoclastogenesis than VIP, and significantly inhibited inflammation-induced osteolysis in vivo. This effect was likely mediated by the VIP receptor, VCAP1, as VCAP2 expression dramatically decreased during osteoclast differentiation. Importantly, SNV previously shown to have an increased stability compared to VIP, showed here significant transepithelial penetration and a clean toxicological profile, presenting a novel drug candidate that could be applied topically to counter both aseptic and infection-related bone destruction.